A review on the influence of process parameters on powder metallurgy parts - Edosa, Osarue Osaruene; Tekweme, Francis Kunzi; Gupta, Kapil (Engineering and Applied Science Research, 2021)
The capability of powder metallurgy (PM) process to produce high quality components/parts is largely dependent on the control of process parameters. To obtain the desirable quality characteristics or properties in the produced part, an appropriate combination of process parameters is required. This paper presents a detailed review of powder metallurgy process parameters and their effects on a wide range of properties while developing a wide range of metallic and composites products. Key process parameters in this study include compaction pressure, sintering temperature, sintering time, sintering atmosphere, lubrication and reinforcement percentage volume. Their influence on physical properties, mechanical properties and microstructure of PM parts are extensively discussed. An extensive literature study as reported in this paper reveals that compaction pressure, sintering temperature, time and sintering atmosphere highly influence part density and strength, whereas part hardness and wear are greatly affected by hard ceramic reinforcement addition, compaction pressure, sintering temperature and time. Die wall lubrication greatly improve the physical, mechanical properties and microstructure of PM components compared to powder mass lubrication. It is observed that the powder metallurgy process conducted at optimum parameters produce quality products. This paper aims to facilitate researchers and scholars by providing a detail knowledge of PM process parameters and their effects, for them to conduct research and development to establish the field further.